Teologi Konstruktif Kitab Mikha Sebagai Kompilasi Sejarah Teks - Yanti, Maria Evvy; Daud, Erwin (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2024)
The Book of Micah is a book that writes prophecies with various interpretations, especially in interpreting the fall of Jerusalem. However, the approach of social history through the compilation of texts shows a variety of interpretations of biblical theology. Some interpret differences in theological messages due to different periods of the social history of parts of the book. Some interpret Micah's theology as a compilation of the orations of the prophet and subsequent writers. Others need to see more consistency between the theology of punishment and salvation in parts of the book's composition. This article aims to find the theology of the Book of Micah as a constructive theology through the compilation of interpretive history. The method used is analyzing the composition structure by paying attention to the history of the compilation and the social situation of the material that makes up the book. The result is that the constructive theology of the Book of Micah encompasses (1) the structure of the Book of Micah alternating between the prophecy of judgment and the prophecy of salvation; (2) the criticism of political leaders and cults; (3) will be consequences of the disobedience of the people; (4) The fulfillment of the prophecy of condemnation as God's justice. Abstrak Kitab Mikha merupakan kitab yang menuliskan nubuatan dengan beragam penafsiran, khususnya dalam menafsirkan mengenai kejatuhan Yerusalem. Namun, pendekatan sejarah sosial melalui kompilasi teks menunjukkan beragam penafsiran teologi kitab. Ada yang menafsirkan terdapat perbedaan pesan teologi karena periode sejarah sosial bagian kitab yang berbeda. Ada yang menafsirkan bahwa teologi Mikha merupakan kompilasi dari orasi nabi dan para penulis selanjutnya. Ada juga yang memandang terdapat ketidakkonsistenan antara teologi penghukuman dan keselamatan pada bagian-bagian komposisi kitab. Tujuan penulisan artikel ini ialah untuk menemukan teologi Kitab Mikha sebagai teologi yang konstruktif melalui sejarah kompilasi penafsiran. Metode yang digunakan ialah analisis struktur komposisi dengan memerhatikan sejarah kompilasi dan situasi sosial materi penyusun kitab. Hasilnya ialah bahwa teologi kontruktif Kitab Mikha meliputi: (1) struktur Kitab Mikha berselang seling antara nubuat penghakiman dan nubuat keselamatan; (2) kritik terhadap para pemimpin politik dan kultus; (3) Akan ada konsekuensi dari ketidaktaan umat; (4) Penggenapan nubuat penghukuman sebagai keadilan Allah.